How to Think like an Atheist: Science, Philosophy, and Religion in Atheist-Produced Educational YouTube Videos - Isomaa, Robin (Approaching Religion, 2024)
Atheism has had a strong presence on YouTube since its founding in the mid-2000s, which coincided with the rise of the new atheism movement, and lay atheists were quick to use the platform to spread new atheist ideas. Drawing from a sample of sixty-five atheist YouTube channels located and observed through online ethnographic methods, this article views YouTube videos as educational resources for atheists. It investigates different types of educational videos and ways of thinking about science, philosophy, and religion that atheist content creators utilize and promote. The analysis reveals that they consistently frame these domains of knowledge through the truth claims they make and generally construct them within a hierarchical framework, with scientific knowledge at the top and religious knowledge at the bottom. Overall, their educational content reproduces new atheist discourses around these subjects, revealing the continuing influence of new atheism, two decades after its emergence. Furthermore, the popularity of videos that debunk arguments from religious apologists suggests that the intended audience of these videos includes both atheists, who are expected to need to learn to defend their atheism in debate with religious others, and “potential atheists”, religious believers who can be deconverted using rational arguments.